Linking two administrative datasets about looked after children: testing feasibility and enhancing understanding - Jade Hooper; Linda Cusworth; Helen Whincup (International Journal of Population Data Science, 2019)
Background with rationale Every year all 32 local authorities in Scotland provide information on looked after children in their area to the Scottish Government. This forms the basis for the annual Children Looked After Statistics (CLAS). Information is also collected by Scottish Children’s Reporter Administration (SCRA) on all children who are involved in the Children’s Hearings System. Until now these two data sets had never been linked.